Hubungan Family Support, Self Care, dan Self Efficacy dengan Kualitas Hidup pada Pasien DM di Puskesmas Kraksaan - Hasanah, Nurul; Rahman, Handono Fatkhur; Khotimah, Husnul (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2024)
Background: Diabetes mellitus is a significant health issue and a non-communicable disease targeted by global leaders for effective management. Objective: This study aims to determine the relationship between family support, self-care, and self-efficacy with the quality of life in patients with diabetes mellitus. Methods: A quantitative, correlational study with a cross-sectional design was conducted. The population consisted of 86 diabetes mellitus patients at Kraksaan Health Center. Sampling was done using the Lemeshow formula, resulting in 86 respondents. Data collection was carried out through closed-ended questionnaires, where respondents selected answers by marking the appropriate option. Bivariate analysis was performed using the Spearman test, and multivariate analysis was done using logistic regression. The study was conducted at Kraksaan Health Center from June to July 2023. Results: Among the tested variables, three independent variables were significantly related to the dependent variable, namely family support (p=0.005), self-care (p=0.00), and self-efficacy (p=0.004). Therefore, these three variables are associated with the quality of life in diabetes mellitus patients.